Design and characterisation of a screen-printed millimetre-wave flexible metasurface using copper ink for communication applications. (17th December 2018) - Falade, Oluyemi P; Jilani, Syeda Fizzah; Ahmed, Abshir Yusuf; Wildsmith, Tom; Reip, Paul; Rajab, Khalid Z; Alomainy, Akram
Abstract: In this paper, the design, fabrication and characterisation of metasurfaces with the anisotropic response for millimetre waves (MMW) has been presented for seamless, secure and low-loss high-frequency communication. Two frequency bands, 29 GHz and 60 GHz, have been selected for the development of efficient, cost-effective and broadband metasurfaces constituting an octa-armed star-shaped structure and a symmetric dual orthogonally I-shaped structure, respectively. Low-cost and high-performance nanoscale printing inks and pastes have been deployed in the screen-printing technique to perform the fabrication of designed metasurfaces on flexible films. Electromagnetic (EM) characteristics of the proposed metasurfaces are evaluated using state-of-the-art testing facilities to demonstrate their potential performance attributes in wave-propagation at MMW for high data rate communication links.